A comparative study of Chinese women 3 × 3 basketball players exercise load in Tokyo Olympic preparation cycle - Wang, Zhe; Cao, Guohuan; Xu, Jiamin; Qiu, Jun; Yang, Ruoyu (Frontiers in Physiology, 2023)
Objective: The aim of this study was to compare the variances in-game loads exhibited by Chinese women's 3x3 basketball team across different stages of the preparation cycle for the Tokyo Olympic Games, and to summarize the fundamental regulations governing Chinese women's 3x3 basketball training and games, in order to establish a theoretical research foundation for the team's new preparation cycle. Methods: This study measured load-related data during the preparation and main competition periods of the 2019-2021 Tokyo Olympics, from April to August 2019 and from April to June 2021. The aim was to compare the changes and differences in a load of competition during different stages and to explore patterns of load changes during the preparation period. This study used wearable devices authorized by FIFA and NBA, along with the Catapult GPS performance monitoring system from Australia (Catapult&Polar Team) as instruments for collecting sports load data. The OptimEye S5 device was worn around the athlete's neck to collect data prior to the game, while the Open Field™ system was utilized for data editing and report generation post-game. Results: Compared to the primary competition load during the 2019 preparation period, the 2021 preparation period exhibited significant increases and decreases (P<0.05) in competition load, high-intensity load, the number of explosive moves, the number of high-intensity acceleration, several changes to the left and right, and the number of explosive jumps. During the 2021 preparation period, the mean heart rate, mean heart rate percentage, and mean speed of the race demonstrated significant decreases in comparison to the race during the 2019 preparation period (P<0.05). Throughout the training period spanning from 2019 to 2021, no significant differences were observed in running distance and maximum speed (P>0.05). Conclusion: The findings of this study reveal that the national training team has fostered positive adaptive changes in athletes, resulting in a significant enhancement in both load and sports performance science data during competition from 2019 to 2021.